PERENCANAAN STRATEGIS SISTEM INFORMASI MENGGUNAKAN METODE WARD AND PEPPARD (STUDI KASUS: SIROPEN) - An-Nisaa Respati Nurcahyengsi (CV. Adiba Aisha Amira, 2026)
The rapid development of Information Technology (IT) and Information Systems (IS) has driven companies to plan and implement appropriate IT strategies to enhance operational efficiency and competitiveness. PT Moya Kasri Wira Jatim, the company managing the Siropen syrup brand, faces challenges in optimizing IT utilization, with a heavy reliance on manual processes in production and limited financial systems. This study aims to formulate an IS/IT strategic plan to improve operational efficiency and strengthen the company’s digital position. Using the Ward and Peppard framework and analytical tools such as PEST, McFarlan’s Strategic Grid, and Value Chain, the research identifies external and internal factors influencing IS/IT implementation. Furthermore, the study proposes technology-based solutions such as an ERP system for process automation, enhanced customer feedback management, and the optimization of e-commerce and real-time inventory management systems. The results indicate that with a well-planned and integrated IS/IT strategy, Siropen can improve efficiency, accelerate data-driven decision-making, and strengthen its competitiveness in an increasingly competitive market.